Multisectoral One Health collaborations across human, animal and environmental health: a protocol paper for an umbrella systematic review of conceptual and analytical approaches to sustainability - Melika Akhbari; Hadjer Nacer; Osman Ahmed Dar (BMJ Open)
Introduction Recent decades have seen a growth in multisectoral and transdisciplinary approaches to improving global health, particularly across human, animal and environmental health-related sciences that advocate for participatory, systems-based perspectives to understanding and promoting health and well-being in the context of social and ecological interactions. For several issues, including human health, animal health and food security, researchers have highlighted the need for transdisciplinary One Health approaches to assess the sustainability of interventions. To understand the current thinking and conceptualisation of sustainability across One Health disciplines, we present a protocol paper for an umbrella systematic review study planned in 2024.Methods and analysis A search strategy based on Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines was developed. The Medline, Embase, Global Health and Web of Science Core Collection were the four databases interrogated through the search strategy and included all articles found in the English language up to 14 April 2024. Meta-analyses, systematic, structured literature reviews and narrative reviews on sustainability will be included and a full-text review of all articles will be undertaken. The articles will be quality appraised using the AMSTAR 2 tool. Data that cover proposed factors influencing and characterising sustainability will be extracted across One Health disciplines including similarities and differences, and a summative content analysis will be completed to identify any emerging themes and develop an analytical framework. The conceptualisation of sustainability in the context of One Health multisectoral approaches will be summarised, a definition of sustainability proposed and include an identification of tools for measuring and assessing sustainability.Ethics and dissemination No primary data will be collected; therefore, ethical approval will not be required. The results will be disseminated in peer-reviewed literature and conference presentations. The findings will also be directly disseminated to the Quadripartite agencies.Prospero registration number CRD42018094031